Measles like syndrome after measles and rubella vaccination - Prasad, Tulsi (International Journal of Contemporary Pediatrics, 2021)
National vaccination program (NIS, IAP) provides vaccination for measles and rubella (MR vaccine) for all children below 15 years of age. After vaccination with live attenuated viruses, the virus replicates on a limited scale. Replication may lead to mild symptoms occurring 5-14 days after MR-vaccination including fever, conjunctivitis and rash but sometimes it leads to florid type of severe rashes which are indistinguishable from a wildtype measles infection. A measles like syndrome may occur following MR vaccination, although it seems to be a rare event and therefore as a pediatrician we must take out time to educate and reassurance the parents about this benign nature and so as to avoid unnecessary problems in future. A 14 year old female child was admitted in our hospital with an impressive (florid) rashes, 7 days after MR vaccination in our vaccination clinic. Diagnostic tests were negative for measles and other infections and was discharged after 7 days of nursing and supportive care. Within 14 days after MR vaccination, a child can present with symptoms very similar to a wildtype measles virus infection. The low incidence of wildtype measles infection after MR vaccination, strongly suggests that these symptoms will likely be a reaction to MR vaccination. To elaborate lots of diagnostic procedures may cause the parents a lot of stress and therefore offering nursing care, supportive care and reassurance to parents may be more appropriate and effective in such cases.